(untitled) (Modern education and development, 2024)
This article fully explains the cyclicality of the economy and macroeconomic instability. There was also talk about the economic cycle, the main types of cycles and the crisis. Данная статья полностью объясняет цикличность экономики и макроэкономическую нестабильность. Также речь шла об экономическом цикле, основных типах циклов и кризисе.